106 Haemorrhagic spinal cord infarct – a rare complication of sympathomimetic amine toxicity. (29th July 2019) - Wall, Ellen L; Leow, Jerome A; Ho, Jonathan; Hwang, Yun T
Abstract : Introduction: Sympathomimetic amines are recreational substances, available illegally as amphetamine derivatives (eg, 'ecstasy' and 'speed'). Ingestion can lead to significant medical complications such as hyperthermia, tachyarrhythmia, seizures and strokes, attributed to catecholamine surge and sympathetic overstimulation. Method: We report an unusual case of sympathomimetic amine ingestion manifesting as hypertension followed by acute onset flaccid paralysis of lower limbs bilaterally and T11 level anaesthesia in a 64 year old woman secondary to haemorrhagic cord infarct. Results: An MRI spine showed features compatible with spinal cord infarction from thoracic level 6/7 to conus associated with cord haemorrhage. There was no evidence of vascular malformations on imaging and the screen for inflammatory myelitides was negative. A urine drug screen tested positive for sympathomimetic amines and the patient acknowledged ingesting a pill of 'unknown identity'. Conclusion: This case highlights a previously unreported complication of recreational sympathomimetics associated with significant patient morbidity. Unfortunately, this woman failed to make significant improvements during admission with ongoing severe motor and sensory deficits of her lower limbs.